2013
DOI: 10.1007/s00381-013-2277-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and endovascular treatment of intracranial arteriovenous malformations in pediatric patients

Abstract: AVM size and deep venous drainage were independently associated with hemorrhage in pediatric patients. Endovascular procedure is feasible and safe for pediatric AVMs, and complete embolization can be achieved in small AVMs, while large AVMs can be adequately reduced in size for additional microsurgery or stereotactic radiosurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 22 publications
2
38
1
Order By: Relevance
“…2,8,19 Only 18%-20% of patients with AVMs present before 15 years of age, 13,17 with hemorrhage and seizure being the most common primary events. 1,5,31,32 Treatment of AVMs includes microsurgical resection, radiosurgery, endovascular embolization, or a combination of these strategies. 3,6,24,28 Accumulating evidence has demonstrated that AVMs recur in children.…”
Section: Discussionmentioning
confidence: 99%
“…2,8,19 Only 18%-20% of patients with AVMs present before 15 years of age, 13,17 with hemorrhage and seizure being the most common primary events. 1,5,31,32 Treatment of AVMs includes microsurgical resection, radiosurgery, endovascular embolization, or a combination of these strategies. 3,6,24,28 Accumulating evidence has demonstrated that AVMs recur in children.…”
Section: Discussionmentioning
confidence: 99%
“…24,26,28 Two larger studies reported results with a relatively distinct bias (a wide range of odds ratio or only radiosurgery patients), suggesting that these studies might have been underpowered to assess the impact of certain features on BAVM hemorrhage. 25,27 In this exclusively pediatric cohort (18 years old or younger) of patients with BAVMs referred to a high-volume Chinese neurosurgery center during the past 5 years, we identified periventricular nidus location and smaller nidus size as independent predictors of hemorrhagic presentation. In contrast to adult patients, deep location, exclusively deep venous drainage, and associated aneurysms were not significantly correlated with the appearance of hemorrhage in these children.…”
Section: Bavm Hemorrhage Risk Predictors In Pediatric Patientsmentioning
confidence: 98%
“…[24][25][26][27][28] Most of these factors and results were obtained from a retrospective cohort (younger than 22 years of age) at Columbia University Medical Center. 24,26,28 Two larger studies reported results with a relatively distinct bias (a wide range of odds ratio or only radiosurgery patients), suggesting that these studies might have been underpowered to assess the impact of certain features on BAVM hemorrhage.…”
Section: Bavm Hemorrhage Risk Predictors In Pediatric Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although AVMs are less common in kids [5], they are still considered the most frequent abnormality of intracranial circulation in childhood [16], and they are the most common cause of spontaneous intraparenchymal hemorrhage in children. Pediatric AVMs could also present with recurrent seizures or headaches [17,18,19,20,21]. The natural history of AVMs in children is not well studied or understood; in part, this might be due to the initial emergent therapy of these lesions.…”
Section: Incidence and Natural Historymentioning
confidence: 99%